Juxtaposition of being professional and becoming professional: lessons from a nationwide study on teachers' conceptions of their professional status - Rizvi, Meher (Frontiers in Education, 2023)
When teachers are being professional in terms of the professional standards they follow in their daily routine to produce quality work, they also wish to be seen as a professional in terms of their status. This is easierly said than accomplished. In Pakistan, teaching has become athe professionemployment of the last resort forof most educated young persons, despite efforts to raise the status of the profession by investing in improving teacher management, developing political will for teacher licensing and investing in teacher development. Whilest there are examples of positive effects of reform initiatives at the classroom level, the current situation is such that these examples mostly go unnoticed due tobecause the reforms generally failinged to make a substantial impact, particularly at the public school classroom level. and tThe teachers continue to be called out lamented overfor their substandard practice and lack of rigorous preparation. The professional status of teachers, therefore, continues to show a downward trend. On the other hand, tTeachers, on the other hand, seem to disagree with the notions that appear to de-professionalize the profession. A large scale nation-wide research was conducted to explore and understand teachers' perspectives on their professional status and the measures that have been taken to enhance teachers' status from a broad perspective using a survey design. Data were collected from 4,165 teachers from the four provinces of Pakistan using a multistage stratified sampling technique to ensure the sample was representative of the entire countryPakistan. The data were analysed using both descriptive and inferential statistical techniques. Factor analysis was used to find the chief underlying dimensions of a set of attributes to unpack teachers' core professional competencies. The research uses the teachers' lens to highlight and discuss the interplay between how theyteachers see themselves as professionals in terms of their status and regard; how they strive to be professionals in terms of practicing professional standards (the being) and how the various teacher education and development measures have been undertaken to enhance teachers' status so that teachers can be seen as a professional (the becoming).